2021
DOI: 10.1016/j.xkme.2020.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient Electronic Health Record Portal Use and Patient-Centered Outcomes in CKD

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Families who used only Dexcom receivers would have had limitations to passive data upload. Emerging studies report that medical record messaging is less utilized and accepted by historically underrepresented individuals, including those from racial and ethnic minority, low-income, and limited English proficiency groups . The lack of linguistically and culturally congruent clinicians, a well-documented national problem, may also have played a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families who used only Dexcom receivers would have had limitations to passive data upload. Emerging studies report that medical record messaging is less utilized and accepted by historically underrepresented individuals, including those from racial and ethnic minority, low-income, and limited English proficiency groups . The lack of linguistically and culturally congruent clinicians, a well-documented national problem, may also have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies report that medical record messaging is less utilized and accepted by historically underrepresented individuals, including those from racial and ethnic minority, low-income, and limited English proficiency groups. 38 , 39 , 40 The lack of linguistically and culturally congruent clinicians, a well-documented national problem, 41 , 42 , 43 may also have played a role. Finally, providing access to CGM, while an important step, does not overcome the structural and social determinants of health, medical racism, health policy, and language barriers that impact health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that access to patient portals resulted in improved diabetes-related outcomes and adherence to hypertensive medication [16,17]. Additionally, a recent study of patients with chronic kidney disease (CKD) found that the use of EHR improves patient-centered outcomes such as CKD-specific knowledge, while reducing CKD-related stress [5]. The ongoing COVID-19 pandemic has accelerated the use of technologies such as patient portals for health care delivery [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Patient portals also provide effective communication tools with the potential to increase patient engagement in self-care management. Patients can also use patient portals for prescription renewal, appointment management, checking lab results, and messaging their providers [ 5 ]. Therefore, the use of patient portals is an increasingly common approach in patient-centered care practices [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Notably, studies have associated patient portal use with better patientreported outcomes, including increased knowledge and reduced disease-related stress. 10 Poor access to portals thereby further exacerbates health care disparities.…”
mentioning
confidence: 99%